DISKRIMINASI IKLAN PEMBERSIH DI TELEVISI DALAM PANDANGAN ISLAM DAN MERVIN DEFLEUR - NAN, ISHA (Universitas Islam Negeri (UIN) Mataram, 2020)
Cleaning ads are one of the commercial advertising models that often appear on television screens. Choosing television as a medium to broadcast advertisements is inseparable from the existence of television capital in influencing audiences, namely its ability to build images and meaning. This power is often used by advertisements in marketing their products. Advertising is often imaged as a product that can solve human problems, especially those related to cleanliness. The construction and delivery of its subtle messages often make audiences fascinated and hypnotized. Even though without realizing it, some hygiene advertisements contain messages that are actually full of discrimination, racism and sarcasm. Islam as a religion teaches that nothing distinguishes between race, color and other primordial identities from one another. From the very beginning, Islam has taught its people to reject all forms of discrimination, including discrimination based on race, color, and others, either openly or in secret. And of course even more dangerous, when discrimination is carried out using mass media, which in fact has the ability to construct images and meanings. Through this paper the author tries to describe how cleaning advertisements are often narrated and some discrimination phenomena that often occur without realizing it.